Public service information technology : the definitive manager's guide to harnessing technology for cost-effective operations and services - Uechi, Edward (Routledge/Productivity Press, 2020)
Public Service Information Technology explains how all areas of IT management work together. Building a computer-based information system is like constructing a house; different disciplines are employed and need to be coordinated. In addition to the technical aspects like computer networking and systems administration, the functional, business, management, and strategic aspects all are equally important. IT is not as simple as expecting to use a software program in three months. Information Technology is a complex field that has multiple working parts that require proper management. This book demystifies how IT operates in an organization, giving the public manager the necessary details to manage Information Technology and to use all of its resources for proper effect. This book is for technical IT managers and non-technical (non-IT) managers and senior executive leaders. Not only will the Chief Information Officer, the IT Director, and the IT Manager find this book invaluable to running an effective IT unit, the Chief Financial Officer, the HR Director, and functional managers will understand their roles in conjunction with the technical team. Every manager at all levels of the organization has a small yet consequential role to play in developing and managing an IT system. With practical guidelines and worksheets provided in the book, both the functional team and the technical team will be able to engage collaboratively to produce a high-quality computer-based information system that everyone involved can be proud to use for many years and that can deliver an effective and timely public program to citizens. This book includes: Multiple layers of security controls your organization can develop and maintain, providing greater protection against cyber threats. Job-related worksheets you can use to strengthen your skills and achieve desired program results. Practices you can apply to maximize the value of your contracts and your relationships with for-profit companies and other contractors. New method for deciding when contracting or outsourcing is appropriate when internal resources are not available. Improved method for estimating intangible benefits (non-financial gains) attributable to a proposed project. An approach to deciding what parts of a business process should or should not be automated, paying critical attention to decision points and document reviews.